2018
DOI: 10.1097/qad.0000000000001817
|View full text |Cite
|
Sign up to set email alerts
|

A week-48 randomized phase-3 trial of darunavir/cobicistat/emtricitabine/tenofovir alafenamide in treatment-naive HIV-1 patients

Abstract: Objectives:To investigate efficacy and safety of a single-tablet regimen of darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF) 800/150/200/10 mg vs. darunavir/cobicistat plus emtricitabine/tenofovir disoproxyl fumarate (TDF) (control) in antiretroviral-treatment-naive, HIV-1-infected adults.Design:Phase-3, randomized, active-controlled, double-blind, international, multicenter, noninferiority study (NCT02431247).Methods:Seven hundred and twenty-five participants were randomized (1 : 1) to D/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
102
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 81 publications
(116 citation statements)
references
References 27 publications
5
102
4
2
Order By: Relevance
“…No grade 3/4 or serious AEs, deaths, or discontinuations due to AEs occurred. The tolerability profile is consistent with earlier studies, with the most commonly reported AEs during the studies, headache and nausea, reported previously for studies of DRV, COBI, FTC, and TAF and in the ongoing phase 3 studies …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…No grade 3/4 or serious AEs, deaths, or discontinuations due to AEs occurred. The tolerability profile is consistent with earlier studies, with the most commonly reported AEs during the studies, headache and nausea, reported previously for studies of DRV, COBI, FTC, and TAF and in the ongoing phase 3 studies …”
Section: Discussionsupporting
confidence: 89%
“…Consistent with other DRV formulations, it is recommended that D/C/F/TAF be taken with food. Also in the ongoing phase 3 studies, the recommended intake for the D/C/F/TAF single‐tablet regimen and other DRV‐containing regimens is with food …”
Section: Discussionmentioning
confidence: 99%
“…Darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF; 800/150/200/10 mg) is an oral once‐daily single‐tablet regimen that is approved in Europe, Canada, and the United States. Studies of the protease inhibitor darunavir have demonstrated a durable virologic response, long‐term safety, and a high barrier to the development of resistance .…”
mentioning
confidence: 99%
“…The efficacy and safety of D/C/F/TAF were demonstrated in 2 pivotal phase 3 clinical trials . In AMBER, D/C/F/TAF was noninferior (10% margin) to darunavir/cobicistat plus emtricitabine/tenofovir disoproxil fumarate in treatment‐naive adults after 48 weeks, with virologic suppression rates of 91.4% and 88.4%, respectively .…”
mentioning
confidence: 99%
See 1 more Smart Citation